A member of the Telenomus californicus Ashmead, 1893 complex parasitizing native cactus moth (Lepidoptera: Pyralidae) eggs in Mexico - Villegas-Luján, Renato; Morales-Gálvez, M.; Plowes, R.; Gilbert, L.; Morales, G. Gallegos-; Bremer, Jonathan S.; Talamas, Elijah; Sánchez-Peña, Sergio (Zootaxa, 2024)
A collection of egg parasitoids in the Scelionidae are identified as members of the Telenomus californicus Ashmead, 1893 complex (californicus+dalmanni+arzamae groups). They were reared from eggs of the cactus zebra worm, Melitara cf. junctoliniella Hulst, 1900 (Pyralidae: Phycitinae) infesting Opuntia streptacantha Lemaire, 1839 (Cactaceae) at Bustamante, Nuevo León, Mexico. Lacking both male specimens and a revision of the complex, no species-level identification could be made. The taxonomic placement of these wasps is discussed as well as possible implementation of these egg parasitoids in new-association biological control of the invasive cactus moth Cactoblastis cactorum (Berg, 1885) (Pyralidae: Phycitinae) in North America.